A simple scoring system to determine axillary lymph node metastasis in carcinoma breast - Masthi, Greeshma K.; Krishnappa, Rohit; S., Rajagopalan (International Surgery Journal, 2019)
Background: The aim of this study is to develop a scoring system wherein axillary lymph node metastasis in carcinoma breast can be predicted preoperatively using simple variables. Methods: A prospective study carried out from December 2017-November 2018 at Rajarajeswari Medical College and Hospital. All clinically node negative cases were included. Data from clinical examination, histopathology report and immunohistochemistry (obtained from trucut biopsy preoperatively) is correlated with presence or absence of lymph node metastasis obtained after modified radical mastectomy. And a scoring system is proposed according to the results obtained. Results: Out of 36 cases studied, 12 cases had score <10, 11 cases had score 11-13, 13 cases had score >14, indicating that more than 50% of cases were over treated with axillary lymph node dissection. Conclusions: Lymph node metastasis in carcinoma breast can be predicted clinically using a scoring system. Further a recommendation for or against axillary node dissection can be made according to the respective scores.